The Tulude Traditional Ceremony In Christian Perspective - Mychael Dimes Antameng (Institut Agama Kristen Negeri Manado, 2020)
Culture, customs and traditions in people's lives, are no longer seen as taboo or should not be tampered with, because of culture, customs and traditions become a bridge in preaching the gospel. Even the Christian community or church is growing in the midst of customs, culture and traditions. Thus there is a role or fair share of culture in the growth of the gospel message. The gospel penetrates all lines of human life including culture, customs and traditions, because